The measure : a novel [compact disc, unabridged] - Erlick, Nikki (Harper Audio ; Blackstone Publishing, 2022)
When every person on every continent receives a small wooden box containing the exact number of years they'll live, the world is thrust into a collective frenzy. Where did these boxes come from?